Probe formation in proton beam writing facility at IAP NASU - Lapin, O.S.; Ponomarev, A.G. (Вопросы атомной науки и техники, 2015)
The principles of a proton beam writing facility were described. Particular attention was paid to the problem of probe-forming system design. It was shown that using of separate systems and parts of the scanning nuclear microprobe is the most effective solution. Various probe-forming system configurations for proton beam writing facility have been investigated. The optimization problem of proton beam formation was solved. On the base of this solution the probe-forming system which has best corresponded to requirements for the lithographic process has been found. Наданo опис принципів побудови каналу протонно-променевої літографії. Особливу увагу приділено завданню щодо створення зондоформуючої системи. Показано, що найбільш ефективним є рішення з використання окремих систем і пристроїв каналу ядерного скануючого мікрозонда. Розглянуто різні конфігурації зондоформуючої системи каналу протонно-променевої літографії. На підставі рішення оптимізаційної задачі з формування пучка протонів знайдена зондоформуюча система, яка найкраще відповідає вимогам для проведення літографічного процесу. Дано описание принципов построения канала протонно-лучевой литографии. Особое внимание уделено задаче по созданию зондоформирующей системы. Показано, что наиболее эффективным решением является использование отдельных систем и устройств канала ядерного сканирующего микрозонда. Рассмотрены различные конфигурации зондоформирующей системы канала протонно-лучевой литографии. На основании решения оптимизационной задачи по формированию пучка протонов найдена зондоформирующая система, которая наилучшим образом отвечает требованиям для проведения литографического процесса.